Development of a simulated Internet for education - Andrew Smith (Association for Learning Technology, 2011)
This paper describes the early stages of research and development of an educational environment designed to enable learners to participate in remote, group based large-scale activities based on local area network and wide area network technologies working on a range of systems and within different learning situations, such as in class group work, remote group work or independent learning. The environment covers specifically routing, switching and wireless principles in the domain of computer networking. This is accomplished using the ‘multiuser functionality' feature found within the Cisco Academy programme, Packet Tracer application. The initial research explores how a ‘virtual Internet' can be implemented to enable learners to engage with the scale and complexity of the Internet without interacting with active routing infrastructures thereby interfering with others. Different communities of interest from Cisco Systems as well as their Academy Programme academic affiliates have contributed to the development of the resource as well as to research into how individuals participate in learning as a result of using this software. This paper tells the story of the iterative action research process with two initial learning situations of ‘remote many' participation and ‘in class many' participation in a large scale networking exercise. As research is still in the development process, this paper explores the experiences and observations gathered from engaging with the two learning scenarios, describing how each interaction exercise was perceived by participants and their educators. Initial findings from both activities indicate that the concept of an ‘Internet on the Internet' to deliver simulated practical learning has considerable potential and brings an alternative dimension to the practical learning experience. Research is ongoing, with the work in this paper informing the continual iterative process.